Regional lung ventilation and perfusion by electrical impedance tomography compared to single-photon emission computed tomography. (20th June 2018) - Hentze, Benjamin; Muders, Thomas; Luepschen, Henning; Maripuu, Enn; Hedenstierna, Göran; Putensen, Christian; Walter, Marian; Leonhardt, Steffen
Abstract: Objective : Electrical impedance tomography (EIT) is a noninvasive imaging modality that allows real-time monitoring of regional lung ventilation ( ) in intensive care patients at bedside. However, for improved guidance of ventilation therapy it would be beneficial to obtain regional ventilation-to-perfusion ratio ( ) by EIT. Approach : In order to further explore the feasibility, we first evaluate a model-based approach, based on semi-negative matrix factorization and a gamma-variate model, to extract regional lung perfusion ( ) from EIT measurements. Subsequently, a combined validation of both and measured by EIT against single-photon emission computed tomography (SPECT) is performed on data acquired as part of a porcine animal trial. Four pigs were ventilated at two different levels of positive end-expiratory pressure (PEEP 0 and 15 cm H2 O, respectively) in randomized order. Repeated injections of an EIT contrast agent (NaCl 10%) and simultaneous SPECT measurements of (81 m Kr gas) and (99 m Tc-labeled albumin) were performed. Main results : Both and from EIT and SPECT were compared by correlation analysis. Very strong ( r 2 = 0.94 to 0.95) correlations were found for and in the dorsal-ventral direction at both PEEP levels. Moderate ( r 2 = 0.36 to 0.46) and moderate to strong ( r 2 = 0.61 to 0.82) correlations resulted for and in the right–left direction, respectively. Significance : The results of combined validation indicate that monitoring of and by EIT is possible. However, care should be taken when trying to quantify by EIT, as imaging artefacts and model bias may void necessary spatial matching.